Paul Creyssel: The 'Forgotten' Voice of Vichy. Issue 1 (16th September 2020) - Chadwick, Kay
Paul Creyssel, Vichy's high-profile Director of Propaganda between 1 April 1942 and 3 March 1943, then Secretary-General for Propaganda until 13 January 1944, is nowadays an all-but-forgotten figure. Found guilty of undermining national morale at his trial in June 1948 after almost four years in detention awaiting judgement, he thereafter faded from public and historical scrutiny. That shift from prominence to obscurity is the focus of this article. It explores the forgotten Creyssel and argues that history's amnesia on such a major player of the Vichy regime was what he himself wanted to engineer. In particular, the article examines how, at his trial, Creyssel's defence was an attempt to reimagine his wartime identity and actions in order to downplay the profile of the man in public memory and record. To develop its line of argument, the article analyses Creyssel's trial papers ― an archive that historians have generally overlooked ― supplemented with reference to his radio broadcasts, which have never previously been comprehensively examined. It identifies specific points that the defence chose to emphasise or understate, or where it was selective with or distorted the truth, and signposts evidence that was disregarded or manipulated in the account given. However, the importance of the case study of Creyssel stretches beyond the individual, for it opens up another version of wartime France and illuminates broader discussions about how collaborators subsequently explained away their activity. Equally, the article sheds light on notions of memory and forgetting in the context of the French experience of the Second World War and beyond, and so connects to discussions on the writing, and 'righting', of narratives of the past. In that light, the article also reflects on how the post-Occupation environment and the shifting context of historical writing contributed to the forgetting of Creyssel. A coda discusses the central place of France's archival holdings for our continuing investigation of Vichy, and reflects on the potential damage caused by recent state-sponsored restrictions on the consultation of such materials.